Enviromental Utilities of Settlement In Bandar Lampung. (Case Study: Kampong Jembatan Beton Way Blau) - A, Hidayatullah; A S, Munawaroh (Bandar Lampung University (UBL), 2017)
The high rates of population growth and urbanization made competition increasingly prevalent residence. Kampong city more and more and allows for the creationof a settlement is not livable. with The good System Utilities Infrastructure at a settlement can make these settlements to be healthy, fit for habitation and give comfort to the peoplewho live in the settlement. This study aims to: determine the existing utility infrastructurein the neighborhood of the Kampong Jembatan Beton Way Blau, knowing the problems that arise in the utility infrastructure in the neighborhood of the Kampong Jembatan BetonWay Blau and know the effort that can be done to make a healthy housing environment. Qualitative Research Methods. The research approach is Literature and case studies.Literature studies were made by outlining a theory about the river and the settlement of Kampong Kota, Theory of utility infrastructure in settlement , residential utilityInfrastructure Standard (SNI) and the Regulation of Cipta Karya (PU). Case Study on Kampong Jembatan Beton Way Blau.